Beyond brown: polyphenol oxidases as enzymes of plant specialized metabolism - Sullivan, Michael L. (Frontiers in Plant Science, 2015)
Most cloned and/or characterized plant polyphenol oxidases (PPOs) have catechol oxidase activity (i.e. they oxidize o-diphenols to o-quinones) and are localized or predicted to be localized to plastids. As a class, they have broad substrate specificity and are associated with browning of produce and other plant materials. Because PPOs are often induced by wounding or pathogen attack, they are most generally believed to play important roles in plant defense responses. However, a few well-characterized PPOs appear to have very specific roles in the biosynthesis of specialized metabolites via both tyrosinase (monophenol oxidase) and catechol oxidase activities. Here we detail a few examples of these and explore the possibility that there may be many more “biosynthetic” PPOs.